Teacher and Peer Feedback on English as an Additional Language Writing: The Role of Social Representations - Rafael Zaccaron; Donesca Cristina Puntel Xhafaj (Universidad Nacional de Colombia, 2024)
This mixed-methods study aims to investigate the bias in peer feedback. Thirty-two English as an additional language learners gave each other anonymous feedback on their texts. Half of the participants received feedback from their teacher disguised as peer feedback, while the other half received actual peer feedback. Data were collected through drafts of two essays, feedback, and a questionnaire. Results indicate that although participants reported trusting teacher feedback more, the quantitative uptake of feedback was similar regardless of the source. Data analysis suggests that the teacher's and peers' social representation plays a more significant role in uptake than the feedback itself.